Corrosion fatigue testing: the combined effect of stress and high temperature corrosion. (4th May 2018) - Chapman, Neil; Brooking, Laurie; Sumner, Joy; Gray, Simon; Nicholls, John
Abstract: A corrosive environment can have a detrimental effect on the fatigue life of a material due to a change in failure mechanism. Attempts have been made to replicate this change on nickel-base superalloy CMSX-4 cast in the <001> orientation. Fatigue testing in air, of this material typically produces a fracture on an angle of approximately 55° which is consistent with the fracture having propagated on a 111 slip plane. The aim of the research was to fatigue test in a corrosive environment with the purpose of producing a crack/fracture which deviated from the typical angle and thus confirm that the corrosive environment had affected the fatigue mechanism. It was concluded that the change in mechanism to high temperature corrosion fatigue was associated with a reduced load application rate together with precorroding the test specimens to trigger the initiation of the corrosion fatigue mechanism.